Work Conditions and the Food Choice Coping Strategies of Employed Parents - Devine, Carol M. (2009)
OBJECTIVE: How work conditions relate to parents’ food choice coping strategies DESIGN: Pilot telephone survey SETTING: Northeastern U.S. city PARTICIPANTS: Black, white, Hispanic employed mothers (25) and fathers (25) randomly recruited from low/moderate income zip codes; 78% of reached and eligible VARIABLES MEASURE(S): Socio-demographic characteristics; work conditions (hours, shift, schedule, job security, satisfaction, food access); food choice coping strategies (22 behavioral items for managing food in response to work and family demands (i.e.: food prepared at/away from home, missing meals, individualizing meals, speeding up, planning)) ANALYSIS: Two-tailed chi-square and Fisher’s exact tests (p=<.05, unless noted) RESULTS: Half or more of respondents often/sometimes used 12 of 22 food choice coping strategies. Long hours and non-standard hours and schedules were positively associated among fathers with take-out meals, missed family meals, prepared entrees, and eating while working; and among mothers with restaurant meals, missed breakfast, and prepared entrees. Job security, satisfaction and food access were also associated with gender-specific strategies. CONCLUSIONS AND IMPLICATIONS: Structural work conditions among parents such as job hours, schedule, satisfaction, and food access are associated with food choice coping strategies with importance for dietary quality. Findings have implications for worksite interventions but need examination in a larger sample.